Predictive Value of Tumor Load in Breast Cancer Sentinel Lymph Nodes for Second Echelon Lymph Node Metastases - C. H. M. van Deurzen; R. van Hillegersberg; M. G. G. Hobbelink; C. A. Seldenrijk; R. Koelemij; P. J. van Diest (Cellular Oncology, 2007)
Background: The need for routine axillary lymph node dissection (ALND) in patients with invasive breast cancer and low-volume sentinel node (SN) involvement is questionable. Accurate prediction of second echelon lymph node involvement could identify those patients most likely to benefit from ALND.